2013
DOI: 10.7577/nbf.460
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities knock: Mediation of peer-relations during meal-time in toddler groups

Abstract: According to socio-cultural perspectives, adults are seen as mediators of cultural believes, values and practices. Qualitative analyses of teachers’ mediation of peer relations based on video-recordings in 9 toddler-groups indicate that meal-time represents opportunities for teachers to facilitate togetherness and peer-relations between toddlers. The teachers might facilitate sharing, passing food, routinized practices such as singing, and conversations. The results indicate variations between child- and group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…The sparse interactions in these groups generally consisted of regulating. These results accorded with several studies on interactions during meals (Hallam et al, 2016;Johansson & Berthelsen, 2014;Klette et al, 2016;Os, 2013;Os & Bjørnestad, in progress). In the high-profile caregivers' groups, the interactions seemed to make use of the potential embedded in meals and included rich, polyadic conversations with various themes (cf.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The sparse interactions in these groups generally consisted of regulating. These results accorded with several studies on interactions during meals (Hallam et al, 2016;Johansson & Berthelsen, 2014;Klette et al, 2016;Os, 2013;Os & Bjørnestad, in progress). In the high-profile caregivers' groups, the interactions seemed to make use of the potential embedded in meals and included rich, polyadic conversations with various themes (cf.…”
Section: Discussionsupporting
confidence: 90%
“…Making the most of these opportunities and potentials is challenging (Hallam, Fouts, Bargreen, & Perkins, 2016;Klette, Drugli, & Aandahl, 2016;Os, 2013;Os & Bjørnestad, in progress). Johansson and Berthelsen (2014) found that intersubjectivity between toddlers and teachers during meals is rare.…”
Section: Meals In Toddler Groupsmentioning
confidence: 99%
See 3 more Smart Citations